Search for long-lived neutral particles decaying into lepton jets in proton-proton collisions at √s= 8TeV with the ATLAS detector - Santos, S. P. Amor dos (2014)
Several models of physics beyond the Standard Model predict neutral particles that decay into final states consisting of collimated jets of light leptons and hadrons (so-called “lepton jets”). These particles can also be long-lived with decay length comparable to, or even larger than, the LHC detectors’ linear dimensions. This paper presents the results of a search for lepton jets in proton-proton collisions at the centre-of-mass energy of √s= 8TeV in a sample of 20.3 fb−1 collected during 2012 with the ATLAS detector at the LHC. Limits on models predicting Higgs boson decays to neutral long-lived lepton jets are derived as a function of the particle’s proper decay length.